Reduced dentin hypersensitivity by nanohydroxyapatite and Salacca zalacca skin extract - Elline, Elline; Prahasti, Anastasia Elsa; Fibryanto, Eko; Mulia, Maria Gresela; Azman, Syuwari Azhar (Routledge Taylor & Francis Group, 2026)
Objective: to determine the potential of the combination of hydroxyapatite and Salacca zalacca skin extract (HAp-SAL) for reducing dentin hypersensitivity by cover-ing the dentinal tubules. Methods: HAp-SAL was mixed in different ratios. Group A is a control, while Groups B, C, and D are groupings of HAp:SAL in 2:1, 1:1, and 1:2 ratios. They were administered to dentin samples for 14 days. Scanning electron microscopy–energy dispersive X-ray (SEM-EDX) analysis was performed. The data was categorized into three categories of dentinal tubule closure. The data were analyzed using the Kruskal–Wallis test to determine the differences between groups. Results: There were significant differences (p < 0.05) between groups. This study showed the formation of mineral deposits on the tubule walls and the accumulation of calcium and phosphate ions surrounding the dentinal tubules. Conclusion: The combination of HAp-SAL skin extract may be able to lessen dentin hypersensitivity by coating dentinal tubules.